Defend or raise? Optimising flood risk reduction strategies. (22nd July 2019) - Lendering, Kasper T.; Jonkman, Sebastiaan N.; van Ledden, Mathijs; Vrijling, Johannes K.
Abstract: Flood risk reduction can be provided by interventions such as raising land or constructing flood defences. This paper introduces an approach to optimise the selection of risk reduction strategies. It expands existing economic optimization approaches for flood defences, by introducing (largely) analytical formulations to include the effects of approaches to mitigate flood consequences. The method considers the size of the protected area and associated damages, the costs and dimensioning of interventions and the likelihood of flooding. It is applied in several practical cases. Within the context of this economic model, we conclude that a system of flood defences is more economical than a landfill for larger areas. Fills are preferred for small areas and/or for low costs. A combination of strategies is preferred when the value protected by the flood defence is low compared to the value protected by the fill, or when the high value development is relatively small in size. The sensitivity of outcomes to the choice of the main input parameters is presented, as well as implications of the results and selection of strategies in developing and developed countries. Overall, this approach supports decision makers in developing effective strategies to manage and reduce flood risk.